CORRELATION BETWEEN BREASTFEEDING AND 3 – 24 MONTHS OLD CHILDREN DEVELOPMENT IN KEPUTIH HEALTH CENTER SURABAYA - Chatrine Evania Palangan Sangka; Sri Umijati; Nur Rochmah (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Children's developmental disorders were increased in Indonesia. One of the factors affecting 3 – 24 months old children development is breastfeeding. However, in several studies, the correlation between the two was still uncertain. This study aimed to determine the correlation between breastfeeding and 3 – 24 months old children development with a cross-sectional study design. Randomly selected 78 mothers who had 3 – 24 months old children at the Keputih Health Center Surabaya. Researchers interviewed mothers about breastfeeding duration and breastfeeding method, as well as their children's development based on Prescreening Developmental Questionnaire (PDQ). Researchers also assessed children's development to answer PDQ. The correlation between breastfeeding and children’s development was then analyzed using the Chi-Square test. Exclusive breastfeeding was widely obtained in children with overall development (83.3%) and fine motor aspects (85.7%) at the appropriate age. Direct breastfeeding was widely obtained in children with speech and language development at the appropriate age (81.9%). Breastfeeding duration was related to overall children’s development (p=0.014) and fine motor aspect (p=0.025). The breastfeeding method was related to children's speech and language aspects (p=0.018). Breastfeeding duration was related to overall children’s development, particularly in the fine motor aspect. The breastfeeding method was related to children's speech and language aspects.